ANALISIS IMPLIKATUR PADA GELAR WICARA MATA NAJWA DI TRANS7 - Ida Ayu Lingga Parwati; Marleni Sepria (Universitas Lampung, 2021)
The conversational implicature is an implicature only known to some people who know the context of the speech. The conversation implicator is trying to analyze the conversation so that a great meaning is obtained. The problems discussed in this study regarding the form and function of the implicature in the Trans Najwa Mata Degree 7. This study aims to describe and explain how the shape and function of the implicature in the Najwa Eye Speech Degree in Trans 7. This study uses descriptive methods. The subject of the study was the conversation contained in the Mata Najwa Speech Degree in Trans 7, so the results of the study showed that there was a principle of cooperation divided into four maxims, namely the quantity maxims, quality maxims, relationship maxims, and method maxims. Implikatur percakapan merupakan implikatur yang hanya diketahui oleh sebagian orang yang mengetahui konteks tuturannya saja. Implikatur percakapan berusaha menganalisis percakapan sehingga diperoleh makna yang besar. Permasalahan yang dibahas dalam penelitian ini mengenai bentuk dan fungsi implikatur dalam Gelar Wicara Mata Najwa Trans 7. Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan bagaimana bentuk dan fungsi implikatur pada Gelar Wicara Mata Najwa di Trans 7. Penelitian ini menggunakan metode deskriptif. Subjek penelitian yaitu percakapan yang terdapat di dalam Gelar Wicara Mata Najwa di Trans 7, sehingga hasil penelitian menunjukkan terdapat prinsip kerja sama yang dibagi atas empat maksim yaitu maksim kuantitas, maksim kualitas, maksim relasi, dan maksim cara.Keywords: Implicature, Principle of Cooperation, Talkshow Mata Najwa Trans7DOI Artikel: https://doi.org/10.23960/J-Simbol/v9i1.2021.7